Status check: Trustee liability to third parties in the conflict of laws - Dickinson, A (Informa Business Intelligence, 2018)
The Privy Council’s decision in Investec Trust (Guernsey) Ltd v Glenalla Properties Ltd 1 is no advertisement for the common law. It serves to demonstrate how legal rules can apparate and take a foothold in the law without any satisfactory foundation. It also illustrates the crude nature of the tools with which judges are equipped to resolve questions of characterisation in cross-border cases. Finally, the decision highlights the curious position of the Privy Council in the United Kingdom’s constitutional structure, and leaves the law in an uncertain and unsatisfactory state.